A recombinant Der p 1-specific allergen-toxin demonstrates superior killing of allergen-reactive IgG+ hybridomas in comparison to its recombinant allergen-drug conjugate. Issue 1 (6th December 2022) - Daramola, A K; Akinrinmade, O A; Fajemisin, E A; Naran, K; Mthembu, N; Hadebe, S; Brombacher, F; Huysamen, A M; Fadeyi, O E; Hunter, R; Barth, S
Summary: Introduction: Current treatments for asthma help to alleviate clinical symptoms but do not cure the disease. In this study, we explored a novel therapeutic approach for the treatment of house dust mite allergen Der p 1induced asthma by aiming to eliminate specific population of B-cells involved in memory IgE response to Der p 1. Materials and Methods: To achieve this aim, we developed and evaluated two different proDer p 1-based fusion proteins; an allergen-toxin (proDer p 1-ETA) and an allergen-drug conjugate (ADC) (proDer p 1-SNAP-AURIF) against Der p 1 reactive hybridomas as an in vitro model for Der p 1 reactive human B-cells. The strategy involved the use of proDer p 1 allergen as a cell-specific ligand to selectively deliver the bacterial protein toxin Pseudomonas exotoxin A (ETA) or the synthetic small molecule toxin Auristatin F (AURIF) into the cytosol of Der p 1 reactive cells for highly efficient cell killing. Results: As such, we demonstrated recombinant proDer p 1 fusion proteins were selectively bound by Der p 1 reactive hybridomas as well as primary IgG1 + B-cells from HDM-sensitized mice. The therapeutic potential of proDer p 1-ETAʹ and proDer p 1-SNAP-AURIF was confirmed by their selective cytotoxic activities on Der p 1 reactive hybridoma cells. The allergen-toxin demonstrated superior cytotoxic activity, with IC50 values in the single digit nanomolar value, compared to the ADC. Discussions: Altogether, the proof-of-concept experiments in this study provide a promising approach for the treatment of patients with house dust mite-driven allergic asthma. Graphical Abstract: